Strategi Pengembangan Inovasi dalam Digitalisasi Untuk Keberlanjutan UMKM di Kelurahan Taman Kecamatan Taman Sidoarjo - Edy Sulistiyawan; Yusuf Iskandar; Siti Istikhoroh; Untung Lasiyono; Wira Yudha Alam; Mohammad Afrizal Miradji (Ekobis Abdimas, 2025)
The current development of digitalization for Micro, Small, and Medium Enterprises (MSMEs) faces increasingly complex challenges in increasing and maintaining competitiveness. Optimization of marketing strategies is very crucial, to ensure that MSMEs can survive, but have an advantage in business competition in the digital era. This study aims to develop innovation in digitalization for the sustainability of MSMEs. The methodology of this study uses qualitative and quantitative analysis through case studies of MSMEs from various industrial sectors. Data was obtained from interviews with MSME survey actors, and analyzing documentation internally. The findings show that MSMEs have succeeded in implementing marketing strategies by innovating from the products they make, managing human resources effectively, utilizing digital technology that continues to develop, and implementing marketing strategies in a targeted manner. This study can be concluded that MSMEs are able to implement digital-based marketing strategies to the development of the business environment and the use of modern technology which are key factors in achieving competitive advantage. MSME recommendations are practically a development in market analysis capabilities, improving digital skills, and implementing structured management practices. The implementation of recommendations for MSMEs is expected to increase competitiveness and contribute more to economic growth locally and nationally.